PERAN MEDIASI KOMUNIKASI ORGANISASI DALAM HUBUNGAN CHANGE READINESS DAN KINERJA OPERASIONAL (STUDI KASUS: BANDARA HUSEIN SASTRANEGARA BANDUNG) - Purnama Safril Hudya; Recky Recky; Gurawan Dayona Ismail; Andhika Mochamad Siddiq; Kartika Nuradina (Jurnal Daya Saing, 2026)
The success of transformation in the airport sector depends not only on the readiness of human resources but also on how effectively communication functions across organizational units. This study focuses on Husein Sastranegara Airport, Bandung, to investigate whether Organizational Communication serves as a bridge (mediator) between Employee Change Readiness and Operational Performance. Employing a quantitative explanatory research design, the study involved the entire population of 65 employees using a total sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), a variance-based structural equation modeling approach, through SmartPLS version 4. Of the five hypotheses tested, two significant relationships were identified: change readiness positively influences communication effectiveness, and communication effectiveness positively influences operational performance. However, the direct relationship between change readiness and operational performance was found to be insignificant. Furthermore, mediation analysis confirmed that organizational communication acts as a significant mediator, indicating that employee readiness for change contributes to operational performance only when supported by an effective organizational communication system